2014
DOI: 10.1088/0953-8984/26/33/333101
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization kinetics of colloidal model suspensions: recent achievements and new perspectives

Abstract: Colloidal model systems allow studying crystallization kinetics under fairly ideal conditions, with rather well-characterized pair interactions and minimized external influences. In complementary approaches experiment, analytic theory and simulation have been employed to study colloidal solidification in great detail. These studies were based on advanced optical methods, careful system characterization and sophisticated numerical methods. Over the last decade, both the effects of the type, strength and range o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
132
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(136 citation statements)
references
References 405 publications
2
132
0
Order By: Relevance
“…(6)} according to the classical nucleation theory is problematic, and hence tests of the theory by experiment can hardly yield conclusive results (see e.g. [37]). In this situation, a computer simulation approach to the problem appears as the most promising choice, but it also encounters conceptual problems: many techniques for obtaining ∆F * of a nucleus require a distinction which particles are part of the crystal and which particles are part of the surrounding fluid [38,39].…”
Section: Introduction and Overviewmentioning
confidence: 99%
“…(6)} according to the classical nucleation theory is problematic, and hence tests of the theory by experiment can hardly yield conclusive results (see e.g. [37]). In this situation, a computer simulation approach to the problem appears as the most promising choice, but it also encounters conceptual problems: many techniques for obtaining ∆F * of a nucleus require a distinction which particles are part of the crystal and which particles are part of the surrounding fluid [38,39].…”
Section: Introduction and Overviewmentioning
confidence: 99%
“…We observe a rich dynamic behavior with the formation and fusion of small clusters resembling molecules, the dynamics of which is governed by an effective conservative energy that decays as 1/r. Breaking the flow symmetry, these clusters can be made active.Colloidal particles acting as "big" artificial atoms have been instrumental in studying microscopic processes in condensed matter, from the kinetics of crystallization [1] to the vapor-liquid interface [2]. Due to their size, colloidal particles are observable directly in real space.…”
mentioning
confidence: 99%
“…[18][19][20] It was found that classical nucleation theory (CNT) and Wilson-Frenkel law, which is usually used in atomic and molecular systems, are also applicable in colloidal crystallization though some challenges were found under some specific conditions. 4,21 Recently, the validity of the classic Ostwald's step rule (conceived by Wilhelm Ostwald as an empirical rule) has also been verified in experia) Author to whom correspondence should be addressed. Electronic mail:…”
Section: Introductionmentioning
confidence: 97%
“…[1][2][3][4][5] Furthermore, the periodic modulation of the refractive index makes it to be an attractive material, photonic crystals, having potential applications in optical fibers, displays, and sensors. [6][7][8] For charged colloidal systems consisting of submicrometer particles and the surrounding medium, one great advantage is that the interparticle interaction potential can be tuned conveniently through particles surface charge, number density, and electrolyte concentration.…”
Section: Introductionmentioning
confidence: 99%